0717 Long-term Experience Of Positive Airway Pressure For The Treatment Of Obstructive Sleep Apnea Syndrome In Youth With Down Syndrome. (12th April 2019) - Xanthopoulos, Melissa S; Beck, Suzanne E; Ku, Helen; Moore, Melisa; Thomas, Jocelyn H; Cielo, Christopher; Smith, Julianne; Matthews, Edward C; Tapia, Ignacio E
Abstract: Introduction: Individuals with Down syndrome (DS) are at increased risk for obstructive sleep apnea syndrome (OSAS), which may not completely resolve after adenotonsillectomy. This has led to an increase in referral for treatment with positive airway pressure (PAP). Treatment with PAP in this group may be challenging. The purpose of this study is to describe the experience of youth with DS and OSAS (DS-OSAS) referred for PAP at a tertiary pediatric sleep center. Methods: Retrospective study of youth with DS-OSAS prescribed PAP between 01/01/14 and 12/31/16. Inclusion criteria: youth with DS-OSAS treated with continuous-(CPAP), bi-level-(BLPAP) or auto-PAP and followed for at least two years after initiation by an interdisciplinary team (physicians, psychologists, nurse practitioner, nurses, and respiratory therapists). Demographic and clinical characteristics were examined. Adherence to PAP at 0-6, 6-12, 12-18, and 18-24 month intervals after initiation was analyzed. Data are presented as mean±SD, median[IQR] or percent. Friedman repeated measures analysis of variance on ranks were performed. Results: 441 children were initiated on PAP. Of these, 61 had DS-OSAS (8.9±5.5 years; 53% females; 56% White), 72% received CPAP and 16.3%, BLPAP. Most completed a titration study (77%). 36% were discharged from the program (transitioned to adult care, moved or resolved); 7% sought alternative treatments; 15% did not tolerate PAP or were lost to follow up. PAP adherence expressed as percentage of nights used and minutes used on nights used was 42.1[17.1-78.6]% and 126[31.8-358.5]mins at 0-6 (N=50); 63.6[14.3-92.4]% and 237[77.0-438.5]mins at 6-12 (N=37); 64.0[7.7-96.4]% and 268.5[83.8-423.2]mins at 12-18 (N=32); and 66[29.0-97.4]% and 219.0[62.0-474.5]mins at 18-24 months (N=26). Of those with adherence data at each interval (N=21), the median minutes used was 184 mins at 0-6, 290 mins at 6-12, 321 mins at 12-18, and 219 mins at 18-24 months (p=0.008). Conclusion: Most children with DS-OSAS tolerated titration polysomnogram and treatment with PAP. A third of patients could be safely discharged. Few children were lost to follow up. Of those with complete data, adherence improved over time. Support (If Any): None